Penerapan Inovasi Proses dan Pemasaran melalui Keselarasan Strategi Bisnis pada UMKM Kabupaten Bandung Barat - Putri Dewi Purnama; Tri Setyowati; Wahyu Rafdinal; Rahma Nadzila Muhammad; Endah Dwi Kusumastuti (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2024)
The community service activities aim to encourage micro, small and medium enterprises (MSMEs) in West Bandung Regency to increase their sales through the implementation of process and marketing innovations. The implementation of this innovation is also carried out by paying attention to the alignment of business strategy. This is implemented to create increased profits through the implementation of innovation and increased sales. The training participants were 32 MSME actors from representatives of 16 sub-districts in West Bandung Regency. The training material for these activities is the application of process innovation and marketing innovation, which includes the application of accounting and bookkeeping theory by processing journal entries, processing ledgers, and preparing financial reports through the SIAPIK application; application of material for determining cost of goods sold (COGS) and practice of calculating COGS; managing business assets; and application of digital marketing materials. Training and mentoring methods, as well as practical simulations are used in this activity. Practical simulation consists of financial recording and bookkeeping, as well as calculating the cost of goods sold (COGS). Meanwhile, data collection for activity uses interviews and questionnaires. Questionnaire data were analyzed using qualitative and quantitative approaches. Evaluation of the completion of this activity is assessing whether there is an increase in competency before and after the training, and assessing the practice of working on questions in the training, as well as the results of mentoring by creating MSME profiles, accounting and bookkeeping records, as well as COGS calculations. Evaluation measurements activity is carried out by giving questionnaires to participants to assess the implementation of activities which include elements of resource persons and training materials. The result of this activity is an increase in participants' understanding of the training theory presented by the presenters.